(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2019)
The present article is about biblical iconography on the Romanesque mural paintings conserved from three churches in Vall de Boí: Sant Climent of Taüll, Santa Maria of Taüll, and Sant Joan of Boí, which at the beginning of the 20th century were moved to the National Museum of Catalan Art in Barcelona. This article analyses the mural paintings of these tree churches, as they were the only way to transmit biblical messages and lessons to illiterate medieval believers. Key words: biblical iconography, Romanesque art, Romanesque mural painting, Vall de Boí.